2020
DOI: 10.3390/jpm11010005
|View full text |Cite
|
Sign up to set email alerts
|

Scoring Osteoarthritis Reliably in Large Joints and the Spine Using Whole-Body CT: OsteoArthritis Computed Tomography-Score (OACT-Score)

Abstract: A standardized method to assess structural osteoarthritis (OA) burden thorough the body lacks from literature. Such a method can be valuable in developing personalized treatments for OA. We developed a reliable scoring system to evaluate OA in large joints and the spine—the OsteoArthritis Computed Tomography (OACT) score, using a convenience sample of 197 whole-body low-dose non-contrast CTs. An atlas, containing example images as reference points for training and scoring, are presented. Each joint was graded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 41 publications
(43 reference statements)
4
25
0
Order By: Relevance
“…Model-5 was trained solely on the CT-AP images PR AUC , area under the precision recall curve; ROC AUC , area under the receiver operating characteristics curve; CI, confidence interval thin-slab maximum intensity projection technique [18]. Turmezei et al based their hip OA grading on three separate assessments of joint space narrowing, osteophytes, and subchondral cysts [10,11]. Their scoring system was diverse, and they reported high reliability, especially for their composite three-class scoring system [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Model-5 was trained solely on the CT-AP images PR AUC , area under the precision recall curve; ROC AUC , area under the receiver operating characteristics curve; CI, confidence interval thin-slab maximum intensity projection technique [18]. Turmezei et al based their hip OA grading on three separate assessments of joint space narrowing, osteophytes, and subchondral cysts [10,11]. Their scoring system was diverse, and they reported high reliability, especially for their composite three-class scoring system [11].…”
Section: Discussionmentioning
confidence: 99%
“…The most common assessment method of radiographic hip OA (rHOA) is the Kellgren and Lawrence (KL) severity grading [ 1 , 2 ]. Clinical computed tomography (CT) has lower resolution than plain radiographs but provides detailed three-dimensional (3-D) information on the joint bones [ 10 , 11 ]. Consequently, due to the differences between the 3-D CT and two-dimensional (2-D) X-ray images, the KL grading is not directly applicable to CT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the previous study, another study using ultrasound found that rectus femoris and vastus lateralis muscle echogenicity, representing fat content and fibrosis, was associated with mobility performance in women with knee OA, while, muscle thickness and subcutaneous fat thickness were not 46 . CT-based grading system to evaluate OA in large joints and the spine, the OsteoArthritis Computed Tomography (OACT) score 47 . This score calculate a person's total OA burden by summing scores of individual joints.…”
Section: Imaging Of Peri-articular Tissues In Oamentioning
confidence: 99%
“…Multiple joints are often affected by osteoarthritis, and this may hamper interpretation of the contribution of a specific joint in patients’ quality of life, physical performance, or biochemical markers. Gielis et al developed and tested the reproducibility of the OsteoArthritis Computed Tomography-Score in order to assess osteoarthritis burden throughout the body in large joints and the spine [ 8 ]. Abnormal new bone formation was observed in patients with diffuse idiopathic skeletal hyperostosis (DISH), especially in the spine near the anterior longitudinal ligament, resulting in an increased risk of spinal fractures.…”
mentioning
confidence: 99%